2011
DOI: 10.1038/pj.2010.140
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects of polyethers and ionic liquids in their binary mixtures on lower critical solution temperature liquid-liquid phase separation

Abstract: The solubility and phase behavior of five polyethers (poly(ethylene oxide), poly(glycidyl methyl ether), poly(ethyl glycidyl ether), poly(ethoxyethyl glycidyl ether) and poly(propylene oxide)) in 14 different room-temperature ionic liquids (ILs) were studied by changing the structures of polyethers and the cations and anions in the ILs. Certain combinations of a polyether and an IL binary mixture exhibited lower critical solution temperature (LCST) phase behavior. For ILs containing the same anions, the polyet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
103
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(116 citation statements)
references
References 60 publications
(85 reference statements)
13
103
0
Order By: Relevance
“…20 C1C3imTFSI has also been investigated as a catalyst for the hydroformylation of alkenes, 21 as an attractive medium for electrodeposition of tantalum, 22 and as a solvent for extraction of aromatic compounds from aliphatic hydrocarbons. 23 Dlubek et al studied C1C3imTFSI using PALS (position annihilation lifetime spectroscopy) and reported a glass transition at a temperature T g ¼ 187 K, a melting transition at a temperature T c ¼ 200 K, and a significant increase in the hole free volume fraction, which determines the temperature-dependence of viscosity, from 0.023 at 185 K to 0.17 at 430 K. 24 Xiao et al have shown that the asymmetry of the C1C3imTFSI cation plays an important role in setting the low-frequency vibrational dynamics of the IL and in determining its relatively low melting point. 25 Pure C1C3imTFSI has been reported with an ionic conductivity of 7.42 Â 10 À3 S cm À1 at 30 C. 26 When doped with the salt LiTFSI in a 1 : 1 molar ratio, the material is reported to exhibit a markedly lower ionic conductivity (e.g.…”
Section: -19mentioning
confidence: 99%
“…20 C1C3imTFSI has also been investigated as a catalyst for the hydroformylation of alkenes, 21 as an attractive medium for electrodeposition of tantalum, 22 and as a solvent for extraction of aromatic compounds from aliphatic hydrocarbons. 23 Dlubek et al studied C1C3imTFSI using PALS (position annihilation lifetime spectroscopy) and reported a glass transition at a temperature T g ¼ 187 K, a melting transition at a temperature T c ¼ 200 K, and a significant increase in the hole free volume fraction, which determines the temperature-dependence of viscosity, from 0.023 at 185 K to 0.17 at 430 K. 24 Xiao et al have shown that the asymmetry of the C1C3imTFSI cation plays an important role in setting the low-frequency vibrational dynamics of the IL and in determining its relatively low melting point. 25 Pure C1C3imTFSI has been reported with an ionic conductivity of 7.42 Â 10 À3 S cm À1 at 30 C. 26 When doped with the salt LiTFSI in a 1 : 1 molar ratio, the material is reported to exhibit a markedly lower ionic conductivity (e.g.…”
Section: -19mentioning
confidence: 99%
“…11,12 For example, poly(N-isopropylacrylamide) (PNIPAm) shows an upper critical solution temperature (UCST) phase transition in certain ILs, which is a completely opposite phenomenon to that observed in aqueous solutions. 13 In contrast, certain polymethacrylates [14][15][16] or polyether derivatives [17][18][19] are found to exhibit lower critical solution temperature (LCST) phase behavior in ILs. Phase transitions of polymers in nonvolatile and thermally stable ILs can afford long-term stable smart materials without solvent evaporation.…”
Section: Introductionmentioning
confidence: 93%
“…Three polyethers with various fractions of PEO were synthesized as previously reported, 53 with the molecular weights (M n ) and polydispersity indexes (PDI) presented in Table 1 Sample Preparation. Polymer/water and polymer/EAN samples with various polymer concentrations (0.1 and 1 wt %) were stirred overnight in a sealed glass vial at room temperature prior to measurements.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%